Parent–child relationship quality and child psychological adjustment in families created using egg donation: children's perspectives at age 5 years. Issue 3 (20th December 2021) - Imrie, S; Lysons, J; Jadva, V; Shaw, K; Grimmel, J; Golombok, S
Abstract: STUDY QUESTION: What are children's perspectives of the quality of their relationships with their parents and their own psychological well-being in families created using egg donation? SUMMARY ANSWER: Children's scores indicated good parent–child relationship quality and high levels of psychological well-being, with children in families created using egg donation rating their relationships with their mothers as higher in warmth/enjoyment than children in a comparison group of families created using IVF. WHAT IS KNOWN ALREADY: Little is known about how children in families created through egg donation view their family relationships and their own psychological well-being. Research with 7-and-10-year-olds in anonymous egg donation families has indicated good parent–child relationship quality from children's perspectives, but studies have not involved younger children or those conceived following identity-release egg donation. STUDY DESIGN, SIZE, DURATION: This study included 50 children who had been born through egg donation and a comparison group of 43 children conceived through IVF with the parents' own gametes. Data were collected between April 2018 and December 2019. The sample forms part of a larger longitudinal study examining family functioning in families created through fertility treatment. PARTICIPANTS/MATERIALS, SETTING, METHODS: Children were aged 5 years old and had been born into families with different-sex couple parents. All families were visited at home. Children were administered the Berkeley Puppet Interview, a standardized assessment of parent–child relationship quality and psychological well-being. MAIN RESULTS AND THE ROLE OF CHANCE: Children in egg donation families rated their relationships with their mothers as higher in warmth and enjoyment than did children in IVF families. No differences were found between the two family types in children's ratings of the father–child relationship, or in children's ratings of their own psychological well-being. LIMITATIONS, REASONS FOR CAUTION: It is possible that children who did not consent to take part in the research had less positive perceptions of their family and themselves than children who participated. WIDER IMPLICATIONS OF THE FINDINGS: The findings are relevant to UK clinics offering identity-release egg donation, to parents who have used egg donation to create their family and to individuals and couples considering their fertility treatment options. That children in egg donation families were more similar than different to children in IVF families in their self-concept and perception of their family relationships should prove reassuring. STUDY FUNDING/COMPETING INTEREST(S): This research was supported by a Wellcome Trust Collaborative Award [208013/Z/17]. The authors have no conflicts of interest to declare. TRIAL REGISTRATION NUMBER: N/A.